GAMBARAN KRISTAL HEMOGLOBIN PADA BERCAK DARAH YANG TERPAPAR PADA BEBERAPA ZAT PEMBERSIH LANTAI DOMESTIK NON KARBOL - Sari, Yessi Gusvita; Asni, Enikarmila; Indrayana, Mohammad Tegar (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTBloodstain is an evidence that often found in criminal case. Bloodstain which is found on a crime scene often already contaminated, there might be an effort to clean up the bloodstain on the floor by using floor cleaner agents. The exposure of cleaning agents potentially damaging membrane cell and denature protein inside the blood, so at the time when forensic examination of bloodstain has been done it is possible to generate different interpretations. This research is a descriptive research with experimental laboratory design to find out the description of haemoglobin crystal on bloodstain exposed by some non carbolic domestic floor cleaner agent using Teichmann test and Takayama test. This research shows that haemoglobin crystal can be found on eighty slide of bloodstain which has been flowed and swabbed by non carbolic domestic floor cleaner agents. The conclusion of this research is no effect of the exposure by non carbolic domestic floor cleaner agent against haemoglobin crystal description on the Teichmann and Takayama test.Keywords : bloodstain, non carbolic domestic floor cleaner agent, Teichmann test, Takayama test